Nominal stress based equal fatigue bearing capacity design of HSLA steel V-shaped butt-welded joints - Xue Wen; Wang Ping; Dong Zhibo; Fang Hongyuan (MATEC Web of Conferences, 2018)
Based on nominal stress, this paper proposed a fatigue life estimation method of V-shaped butt welded joints. Then, the fatigue bearing capacity of the base metal under the same fatigue load was used as design goal of the V-shaped butt welded joints and an equal fatigue bearing capacity (EFBC) design method for V-shaped butt welds was thus formed. High strength low alloy steel Q690 was chosen as the experimental material to carry out the equal fatigue bearing capacity design.